FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI BALITA USIA 1-5 TAHUN DI POSYANDU KINASIH, KADIPIRO, SURAKARTA - Dheny Rohmatika; Maula Mar’atus Solikhah (Journal of Advanced Nursing and Health Sciences, 2021)
In toddlerhood, children are experiencing a very rapid growth process that requires relatively more food substances with higher quality. The results of nutrition and growth into adulthood, are very dependent on nutritional and health conditions during toddlers. Malnutrition or malnutrition in infants and children, especially at the age of less than 5 years can result in disruption of physical growth and brain intelligence. In general, there are 4 main problems of malnutrition in Indonesia, namely PEM (Protein Energy Deficiency), Iron Nutrient Anemia, Lack of Vitamin A and Disorders due to lack of iodine. One of the most fatal effects of protein deficiency is positively correlated with infant mortality. The factors that influence the nutritional status of toddlers are numerous, including income, knowledge of maternal nutrition, access to health services, incidence of diarrhea, exclusive breastfeeding, sources of clean water, parenting patterns, nutrition during pregnancy and low birth weight. LBW). This study aims to determine the factors associated with the nutritional status of toddlers aged 1-5 years at the Kinasih posyandu. The type of research is quantitative research, with a cross sectional study approach. The sample of this research is 40 children under five, taken by purposive sampling. Nutritional status data based on anthropometric measurements of BW/U were compared with the WHO_NCHS Z-score value. The results showed that there was a significant relationship between nutritional status and mother's knowledge (p=0.000), mother's education (p=0.000), nutritional status (p=0.012). While the variables that did not exist were significantly related to nutritional status with the number of family members (p = 0.973).